Industry 4.0 in Portugal - The state of the art - Pereira, A. (2023)
The fourth industrial revolution aims to transform industrial units into more efficient and productive organisations, through the implementation of technologies based on digital and intelligent systems. This research assesses the level of implementation of the ‘Industry 4.0’ concept in Portugal, identifying its benefits and difficulties, and also seeking to identify the best tool to assess the level of I4.0. To this end, a qualitative approach was used, supported by 18 interviews with industrial managers. The research shows that there is no integrated view of the I4.0 concept, although the results demonstrate a concern of companies with the subject, with actions aiming to implement the concept in their organisations, where the main barriers are found at the level of investment needed and change management. As to the benefits, it is highlighted the increases in productivity and the reduction of errors in the process.